De eeuw van Rubens. - Roberts-Jones, Ph.; van Puyvelde, Leo; Lebeer, L.; Jansen, Ad. (Brussel : Koninklijke Musea voor Schone Kunsten van België, 1965)
Adriaenssen, Alexander ; van Alsloot, Denys ; d'Arthois, Jacob ; van Balen, Hendrik ; Beert, Osias ; Boeckhorst, Jan ; Boel, Pieter ; Boucquet, Victor ; Bouillon, Michel ; Breughel, Abraham ; Breughel de Oude, Jan ; Breughel de Jonge, Jan ; Breughel, Jan-Pieter ; Brouwer, Adriaen ; Carlier, Jean-Guillaume ; de Champaigne, Philippe ; De Clerck, Hendrik ; Coques, Gonzales ; Cossiers, Jan ; van Craesbeeck, Joos ; De Crayer, Gaspar ; van Diepenbeek, Abraham ; Douffet, Gérard ; van Dyck, Antoon ; van Eertvelt, Andries ; van Es, Jacob ; Finsonius, Ludovicus ; Flémalle, Bertholet ; Franchoys, Pieter ; Francken de Jonge, Frans ; Francken de Jonge, Hiëronymus ; Fyt, Jan ; Goubeau, Antoon ; Govaerts, Abraham ; Van den Hecken, Samuel ; De Heem, Jan Davidsz. ; van Heil, Daniël ; van Herp, Willem ; Van den Hoecke, Robert ; Janssens, Abraham ; Janssens, Jeroom ; Jordaens, Jacob ; Keirinckx, Alexander ; van Kessel de Oude, Jan ; van Kessel de Jonge, Jan ; De Keuninck, Kerstiaen ; de Lairesse, Gérard ; Rombouts, Theodoor ; Rubens, Pieter Paul ; van Oost, Jacob ; Peeters, Bonaventura ; Peeters, Clara ; Peeters de Oude, Jan ; Pourbus de Jonge, Frans ; Primo, Luigi ; Quellinus, Ersamus ; Ryckaert III, David ; Sallaert, Antoon ; Savery, Roelandt ; Schoevaerdts, Matthaeus ; Schut, Cornelis ; Seghers, Daniël ; Siberechts, Jan ; Snayers, Peter ; Snellinck, Andries ; Snyders, Frans ; van Son, Joris ; van Stalbemt, Adriaen ; Sutermans, Justus ; Sweerts, Michiel ; Teniers de Jonge, David ; van Thulden, Theodoor ; van Tilborgh, Gillis ; van Uden, Lucas ; van Utrecht, Adriaen ; De Vadder, Lodewijk ; van Veen, Otto ; van Veerendael, Nikolaas ; Vinckboons, David ; De Vos, Cornelis ; De Vos, Paul ; Vrancx, Sebastiaan ; Wildens, Jan ; Wolfvoet de Jonge, Victor ; Ykens, Catharina ; Ykens, Frans ; Zegers, Gerard ; Breughel, Ambrosius ; De Momper de jonge, Joos ; Neyts, Gillis ; Quellinus, Jan-Erasmus ; De Wael, Cornelis ; van Avont, Pieter ; Baudewijns, Adriaen-Frans
Boel, Coryn (Quiryn) ; a Bolswert, Boëtius ; a Bolswert, Schelte (Schelderic) ; Bonnecroy, Jan-Baptiste ; Borrekens, Mathijs ; Bosschaert, Thomas Willeboirts ; Van der Bruggen, Jan ; Coelemans, Jacob ; Edelinck, Gerard ; Galle I, Cornelis ; Genoels, Abraham ; Van de Hecke de Oude, Jan ; Jegher, Christoffel ; De Jode de Jonge, Pieter ; de Lairesse, Gérard ; Lauwers, Nikolaas ; Miel, Jan ; van Nieulandt, Willem ; Plattenberg, Matheus ; Pontius, Paulus ; Serwouters, Pieter ; Soutman, Pieter ; Van der Stock, Ignatius ; van Ieper, Jan Thomas ; van Thulden, Theodoor ; Vosterman, de Oude, Lucas ; Van de Wijngaerde, Frans ; van Beveren, Mattheus ; Cardon, Johannes ; Del Cour, Jean ; du Quesnoy, Frans ; du Quesnoy de Jonge, Hiëronymus ; Faydherbe, Lucas ; de Grupello, Gabriël ; Kerricx, Willem ; De Nole, Andries ; Quellien de Oude, Artus ; Quellien de Jonge, Artus ; Scheemaeckers, Pieter ; Verbrugghen, Hendrik Frans ; Verbrugghen de Oude, Pieter
De eeuw van Rubens, Koninklijke Musea voor Schone Kunsten van België, Brussel, 15 oktober - 12 december 1965
boek